Prospects of TA in Sales Management - Sharma, Pooja (Journal of Commerce and Trade, 2009)
Interaction is a word that is used frequently when we talk of relationships. Why do you interact? Probably to share your feelings and thoughts. Man is a social animal. There is a basic need of every person to communicate and interact with other people. This communication is carried out in any one of the three forms, i.e. verbally, non-verbally and through written communication. Each of these three forms of communication is instrumental in getting your message across to the other party. The importance of communication probably stems from the fact that the requirements of people differ and all people are different when it comes to their attitudes and behavior. Thus a salesperson has to master this art of communication – so as to understand people well while communicating with them, and produce the maximum number of successful call closes. Even in organizations the style of communication keeps on changing based on the size and culture of the organization. Inspite of all the variations that can happen in the workplace, the salesperson is expected to produce results consistently. Salespersons have certain key characteristics that distinguish him from people in other trades. Once these characteristics are inculcated in the salesperson, he can perform inspite of variations, and is highly adaptable in workplace and during interactions with customers. In this paper we will look at the crucial parameters that make the salesperson a success in organizational communication.